Forest Africa Zambia Ltd: Agri-Innovation Report - Dahl, H.; Njiru, A.; Sewe, L.; Dlamini, J.; Nortje, K.; Nowak, Andreea C.; Giombini, V.; Ires, I.; Alamu, E.O. (International Institute of Tropical Agriculture, 2023)
This report presents the consolidated outputs of the CGIAR researchers involved in the first cohort of the CGIAR Food Systems Accelerator. The first half of the report describes the methods that were applied, the second half presents the results. The Food Systems Accelerator was established to bolster Ukama Ustawi, a CGIAR initiative focused on transforming agri-food systems in East and Southern Africa (ESA). This program, spanning from 2022 to 2024, aligned scientists with agribusinesses to bring CGIAR innovations to scale in ESA. It achieved its objectives by providing CSA Technical Assistance to agribusinesses, enabling the adoption of climate-smart agricultural practices and de-risking their operations. Furthermore, the program offered Impact Measurement and Management support, helping agribusinesses measure and manage their environmental and social impacts effectively. Lastly, it provided Investment Readiness Technical Assistance to increase the agribusinesses’ capacity to absorb capital, facilitating their access to funding for sustainable growth and ecological impact. By combining science-driven support and investment readiness, the Food Systems Accelerator Program aims to ensure resilient and sustainable agribusiness development in ESA.